Interactions between Health Searchers and Search Engines - Schoenherr, Georg P.; White, Ryen W. (37th Annual International ACM SIGIR Conference on Research and Development in Information Retrieval (SIGIR 2014), Gold Coast, Australia, 2014)
The Web is an important resource for understanding and diagnosing medical conditions. Based on exposure to online content, people may develop undue health concerns, believ- ing that common and benign symptoms are explained by se- rious illnesses. In this paper, we investigate potential strate- gies to mine queries and searcher histories for clues that could help search engines choose the most appropriate infor- mation to present in response to exploratory medical queries. To do this, we performed a longitudinal study of health search behavior using the logs of a popular Web search en- gine. We found that query variations which might appear innocuous (e.g. "bad headache" vs "severe headache") may hold valuable information about the searcher which could be used by search engines to improve performance. Fur- thermore, we investigated how medically-concerned users re- spond differently to search engine result pages (SERPs) and find that their disposition for clicking on concerning pages is pronounced, potentially leading to a self-reinforcement of concern. Finally, we studied to which degree variations in the SERP impact future search and real-world health- seeking behavior and obtained some surprising results (e.g., viewing concerning pages may lead to a short-term reduction of in-world healthcare utilization).